PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA SEBLAK KUY BANDAR LAMPUNG - Sofiana, Ananda Mery; Dewi, Cahya Komala; Purnama, Wijaya; Sanjaya, Vicky F (Faculty of economcs Universitas Singaperbangsa Karawang, 2022)
This research aims to test and analyze the influence of quality and price on product purchases (case study of seblak kuy consumers). This research was carried out using descriptive and verification methods, namely: collecting, presenting, analyzing and testing hypotheses, as well as making conclusions and suggestions. The sample in this study consisted of 90 respondents. The results of this research are that there is a strong correlation between service quality and price. Partially there is an influence of service quality on purchasing decisions. And there is an influence of price on purchasing decisions. Meanwhile, simultaneously there is an influence of service quality and price on purchasing decisions.